Digital Literacy, Entrepreneurial Orientation, and Product Innovation as Drivers of MSME Performance: Unpacking the Moderating Role of Government Support through a Systematic Literature Review - Mutiara Meiyana; Muhammad Iqbal Fasa (Institut Agama Islam Negeri Palopo, 2026)
The digital transformation of business has increased the importance of strategic capabilities in enhancing the performance of micro, small, and medium enterprises (MSMEs). However, previous studies examining digital literacy, entrepreneurial orientation, product innovation, and government support remain fragmented. This study aims to systematically synthesize the existing literature and develop an integrated conceptual framework based on the Resource-Based View (RBV), Dynamic Capability Theory (DCT), and Institutional Theory. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines using peer-reviewed articles indexed in Scopus and Web of Science published between 2015 and 2026. The findings reveal that digital literacy, entrepreneurial orientation, and product innovation significantly enhance MSME performance, while government support strengthens these relationships through enabling institutional conditions. This study contributes by proposing an integrated framework that explains the interaction between internal strategic capabilities and external institutional support, offering valuable insights for researchers, practitioners, and policymakers to improve MSME competitiveness in the digital economy. Keywords: Digital Literacy; Entrepreneurial Orientation; Product Innovation; Government Support; MSME Performance; Systematic Literature Review.